(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
This study aims to evaluate the level of digital transformation by identifying the reality of digital transformation and its requirements in Libyan universities, Sabratha University as a model, as well as the impact of obstacles that limit its achievement and the standards that must be met to achieve digitization in the university. The researcher used the descriptive analytical approach, where questionnaires and interviews were used to collect data, in addition to analyzing some official university documents. A questionnaire form was designed as the main tool for the study and distributed to the targeted sample of faculty members at the university and some interviews with faculty members, where the study sample amounted to 150 respondents, and 106 items were obtained that matched the study’s answers and questions. Among the most important results reached by the study: the study individuals showed a low trend of 61.0% towards the reality of digital transformation and its requirements within the university, and by 69.4% there is an impact of obstacles that limit the effectiveness of digital transformation. The study proposes recommendations to improve the efficiency of digital transformation and enhance integration between technology and the educational process.